PENERAPAN MEDIA PUZZLE UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN SISWA KELAS I SDN 16 SUNGAI GOA (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This research was conducted to improve the beginning reading skills of first grade students at SDN 16 Sungai Goa by using puzzle media as a teaching aid. Classroom action research was carried out in three cycles using the Kurt Lewin model, involving 16 students (eight boys and eight girls) in the even semester of the Academic Year 2021/2022. Data collection instruments used were tests, observation sheets, and field notes. The results showed that in cycle I, the students' success rate in reading only reached 55.56% and the learning activities conducted by the teacher only reached 63.23%. In cycle II, the students' success rate increased to 82.5% and the teacher's learning activities reached 85%. Meanwhile, in cycle III, the students' success rate increased to 95.05% and the teacher's learning activities reached 93.75%. This research showed that the use of puzzle media in beginning reading instruction can improve the reading skills of first grade students at SDN 16 Sungai Goa. In addition, puzzle media can make learning more enjoyable and effective. Therefore, it is recommended for teachers to design reading instruction well and use game activities such as puzzle media in instruction to increase students' interest in reading.